Analysing Similarity in Exam Timetabling - Burke, Edmund; Eckersley, Adam; McCollum, Barry; Petrovic, Sanja; Qu, Rong (2004)
In this paper we carry out an investigation of some of the major features of exam timetabling problems with a view to developing a similarity measure. This similarity measure will be used within a case-based reasoning (CBR) system to match a new problem with one from a case-based of previously solved problems. The case base will also store the heuristic for meta-heuristic techniques applied most successfully to each problem stored. The technique(s) stored with the matched case will be retrieved and applied to the new case. The CBR assumption in our system is that similar problems can be solved equally well by the same technique.